Digital Transformation in Education: Exploring 21st Century Teaching Strategies for Effective Learning - Ibnu Fitrianto (Yayasan Azhar Amanaa Yogyakarta, 2026)
Digital transformation has become a central issue in contemporary education, particularly in the development of effective teaching strategies that align with the demands of twenty-first century learning. This study aims to explore how digital technologies support innovative teaching practices and enhance learning effectiveness in higher education. The research employed a qualitative research design using a case study approach to examine the implementation of digital teaching strategies in university classrooms. Data were collected through semi-structured interviews with lecturers, classroom observations, and analysis of institutional documents related to digital learning initiatives. The data were analyzed using thematic analysis to identify key patterns and themes related to digital transformation in teaching and learning practices. The findings reveal that the integration of digital platforms, collaborative tools, and multimedia resources has significantly improved student engagement, promoted student-centered learning, and supported flexible learning environments. In addition, digital transformation encourages the development of essential twenty-first century competencies such as digital literacy, collaboration, and critical thinking. However, the study also identifies several challenges, including limitations in technological infrastructure and the need for continuous professional development for educators. Overall, the results suggest that successful digital transformation in education requires strong institutional support, adequate technological resources, and the readiness of educators to adopt innovative pedagogical strategies. This study contributes to the growing body of literature on digital education by highlighting the role of digital technologies in fostering more interactive and effective learning environments in higher education.